The Influence of Work Environment, Work Discipline and Leadership on the Performance of State Civil Apparatus at the Padang Guci Hulu District Office, Kaur Regency - Tinsi Afriani; Nia Indriasari; Abdul Rahman (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This research aims to know influence of the work environment, work discipline and leadership on State Civil Apparatus performance at Padang Guci Hulu District Office of Kaur Regency. Data were collected through questionnaire methods using census techniques to 22 employee poeple at Padang Guci Hulu District Office. Data processing manually uses multiple regression analysis, the coefficient of determination and hypothesis testing through with t test and F test/Anova. The result of the regression analysis showed